Cu < 2 + >-doped PbBiO2Br catalyst as well as preparation method and application thereof

Through Cu2+ doped PbBiO2Br catalyst and photoultrasonic vibration coupling technology, the problem of low efficiency of existing photocatalysts is solved, efficient nitrogen to ammonia conversion and pollutant degradation are achieved, and the development of hydrogen energy storage is promoted.

CN119140126APending Publication Date: 2024-12-17ZHEJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411452487.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing photocatalysts have low efficiency in nitrogen to ammonia conversion and pollutant degradation, and lack efficient and inexpensive ammonia production methods, which limits the development of hydrogen energy storage and use.

Method used

Cu2+ doped PbBiO2Br catalyst is prepared by hydrothermal reaction and annealing, combined with light and ultrasonic vibration field coupling technology, the energy band gap, light absorption capacity and piezoelectric properties of the catalyst are improved, and carrier separation and nitrogen fixation reaction are promoted.

Benefits of technology

It significantly improves the nitrogen fixation efficiency and catalytic performance of the photocatalyst, achieves efficient ammonia generation and pollutant degradation, and has the characteristics of stability and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140126A_ABST
    Figure CN119140126A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu < 2 + >-doped PbBiO2Br catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. In the chemical composition of the Cu < 2 + >-doped PbBiO2Br catalyst, the molar ratio of Cu < 2 + > to PbBiO2Br is x%, and x is more than or equal to 0.5 and less than or equal to 2. According to the invention, Cu < 2 + > is doped with PbBiO2Br to form a solid solution, so that the migration and separation efficiency of carriers in a material bulk phase is changed. In addition, the doping of Cu < 2 + > can promote the generation of oxygen vacancies, enhance the adsorption and activation of N2, and facilitate the proceeding of nitrogen fixation reaction. PbBiO2Br is applied to light and ultrasonic vibration coupling catalytic nitrogen fixation for the first time, and the synergistic effect of PbBiO2Br and light and ultrasonic vibration coupling catalytic nitrogen fixation is successfully achieved. According to the invention, a novel efficient photocatalytic material is designed from ion doping and ultrasonic vibration field coupling, and the photocatalytic material has remarkable innovativeness in the fields of catalyst design and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a Cu 2+ Doped PbBiO2Br catalyst, preparation method and application thereof. Background Art

[0002] Hydrogen energy is one of the most ideal solutions to replace fossil energy, but it is limited by the storage and production of hydrogen. Ammonia is a better hydrogen storage fuel than hydrogen, with the advantages of easy liquefaction, convenient storage and transportation, and high energy density. However, the production of ammonia also faces the problems of high cost and high energy consumption, and is accompanied by a large amount of greenhouse gas CO2 emissions. In order to realize the hydrogen energy system with ammonia as the carrier, it is urgent to develop cheap, efficient, and green ammonia synthesis methods. The use of renewable energy (solar energy, wind energy, etc.) to achieve the conversion of nitrogen (N2) to ammonia is regarded as a promising approach. Among them, photocatalytic nitrogen fixation has attracted attention for its low cost and environmental advantages. Since Schrauzer et al. first realized the conversion of nitrogen to ammonia under light on TiO2 materials in 1975, although the efficiency of the catalyst has been improved, it is still far from practical application. This situation is also suitable for photocatalytic pollutant degradation, and the development of more efficient photocatalytic materials has always been the core goal of research.

[0003] The research and development of efficient photocatalytic materials is the key to the development of photocatalytic technology. The current design of photocatalysts mainly focuses on the modification of the internal structure of the material, but this method is limited by the characteristics of the material itself. In contrast, external field coupling technology provides more possibilities for performance improvement. When external fields such as heat, electricity, magnetism, microwaves, and ultrasound are introduced, the corresponding energy can be transferred to the photocatalytic system, activating the reaction molecules and promoting the separation of photogenerated carriers, thereby significantly improving the photocatalytic efficiency. In recent years, ultrasonic vibration field coupling technology has received widespread attention. Through the cavitation effect of the medium water, ultrasound provides mechanical impact force to the catalytic material, causing it to deform and excite a piezoelectric field, thereby promoting the separation of photogenerated carriers and greatly improving the photocatalytic efficiency. Summary of the invention

[0004] The object of the present invention is to provide a Cu 2+ Doped PbBiO2Br catalyst; Another object of the present invention is to provide a Cu 2+ Preparation method of doped PbBiO2Br catalyst; Another object of the present invention is to provide a Cu 2+ Application of doped PbBiO2Br catalyst.

[0005] The present invention provides a Cu 2+ Doped PbBiO2Br catalyst, chemical composition, Cu 2+The molar ratio to PbBiO2Br is x%, where 0.5≤x≤2.

[0006] Furthermore, Cu 2+ The molar ratio of Cu to PbBiO2Br is 1%. 2+ When the doping ratio is controlled within this range, the catalytic efficiency of the catalyst is the highest.

[0007] Furthermore, the energy band gap of the catalyst is 2.48 eV. 2+ The doping of reduces the energy band gap of PbBiO2Br and improves its light absorption capacity; it reduces the work function of PbBiO2Br and promotes the migration and separation of carriers; in addition, it increases the disorder of the PbBiO2Br lattice and enhances its piezoelectric properties. These three changes effectively improve the catalytic nitrogen fixation efficiency of the catalyst.

[0008] Hydrothermal reaction is a chemical reaction carried out under high temperature and high pressure conditions, usually in a closed reactor (such as an autoclave). This reaction method uses water as a solvent to promote the dissolution, crystallization, decomposition or synthesis of substances under high temperature and high pressure.

[0009] The present invention also provides a Cu 2+ The preparation method of the doped PbBiO2Br catalyst comprises the following steps:

[0010] S1: dissolving bismuth nitrate in a first solvent, and then mixing the mixture with polyvinyl pyrrolidone and water;

[0011] S2: uniformly mixing the mixed solution obtained in step S1 with lead nitrate and sodium bromide;

[0012] S3: uniformly mixing the mixed solution obtained in step S2 and copper nitrate, adding a pH adjuster, adjusting the pH of the mixed solution to 11, and uniformly mixing;

[0013] S4: subjecting the mixed solution obtained in step S3 to a hydrothermal reaction at 170-180° C. for 10-14 h, cooling, performing solid-liquid separation on the obtained reaction solution, washing the solid, and drying;

[0014] S5: The solid obtained in step S4 is calcined at high temperature to obtain the Cu 2+ Doped PbBiO2Br catalyst.

[0015] The hydrothermal combined with annealing method is simple in process, easy to operate, and suitable for large-scale preparation. 2+ The PbBiO2Br-doped material has both photocatalytic and vibrational catalytic properties.

[0016] Furthermore, the pH regulator is an aqueous solution of sodium hydroxide; the concentration of the aqueous solution of sodium hydroxide is 20-30 mol / L.

[0017] Furthermore, the solid is centrifugally washed using a mixed solution of water and alcohol; the washed solid is dried at 55-65° C. for 10-14 hours.

[0018] Furthermore, in step S1, the first solvent is nitric acid; and the concentration of the nitric acid is 6 mol / L.

[0019] Further, the molar ratio of the bismuth nitrate to the nitric acid is 1:(1.5-2.5). Preferably, the molar ratio of the bismuth nitrate to the nitric acid is 1:2.

[0020] Furthermore, the molar ratio of the bismuth nitrate, the lead nitrate, and the sodium bromide is 1:1:1; the molar ratio of the added mass of the polyvinyl pyrrolidone to the bismuth nitrate is (1.5-2.5) g:0.03 mol. Preferably, the molar ratio of the added mass of the polyvinyl pyrrolidone to the bismuth nitrate is 2 g:0.03 mol.

[0021] Furthermore, in step S4, the volume ratio of the mole of bismuth nitrate to the solution in the hydrothermal reaction is (2.9-3.1) mmol:80 mL.

[0022] Furthermore, in step S5, the high temperature calcination temperature is 350-450° C. and the calcination time is 1.5-2.5 h.

[0023] The present invention also provides a Cu 2+ Application of doped PbBiO2Br catalysts, such as Cu 2+ The doped PbBiO2Br catalyst is used for photocatalytic and / or ultrasonic catalytic nitrogen fixation and photocatalytic degradation of RhB.

[0024] The present invention discloses a Cu 2+ PbBiO2Br catalyst was doped with Cu 2+ Doping PbBiO2Br forms a solid solution, changing the migration and separation efficiency of carriers in the bulk phase of the material. 2+ The incorporation of can also promote the generation of oxygen vacancies, enhance the adsorption and activation of N2, and facilitate the nitrogen fixation reaction. This invention is the first to apply PbBiO2Br to light + ultrasonic vibration coupling catalytic nitrogen fixation, successfully achieving the synergistic effect of the two. In addition, Cu 2+ There are no reports on PbBiO2Br-doped catalysts in the field of photocatalysis and ultrasonic vibration catalysis. 2+The catalyst doped with PbBiO2Br is more excellent than pure PbBiO2Br in photocatalytic degradation of dyes. The present invention designs a new type of highly efficient photocatalytic material by coupling ion doping and ultrasonic vibration field, which is significantly innovative in the field of catalyst design and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the X-ray powder diffraction (XRD) spectra of Example 2 and Comparative Example 1 of the present invention;

[0026] Figure 2 is the Raman spectra of Example 2 and Comparative Example 1 of the present invention;

[0027] Figure 3 is an X-ray photoelectron spectroscopy (XPS) diagram of Example 2 and Comparative Example 1 of the present invention;

[0028] Figure 4 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of Comparative Example 1 (ac) and Example 3 (ef) of the present invention are shown;

[0029] Figure 5 The UV-visible diffuse reflectance spectra (DRS) of Example 2 and Comparative Example 1 of the present invention are shown;

[0030] Figure 6 The photocatalytic nitrogen fixation performance test results of Examples 1-4 and Comparative Example 1 of the present invention are shown in FIG.

[0031] Figure 7 This is a photocatalytic nitrogen fixation cycle test result diagram of Example 2 of the present invention;

[0032] Figure 8 This is a graph showing the test results of light-vibration catalytic nitrogen fixation in Example 2 of the present invention;

[0033] Fig. 9 This is a graph showing the test results of light-vibration catalytic nitrogen fixation in Comparative Example 1 of the present invention;

[0034] Fig.10 The figure is a graph of the electrochemical impedance spectroscopy (EIS) test results of Example 2 and Comparative Example 1 of the present invention;

[0035] Fig.11 This is a transient current response diagram of Example 2 of the present invention under light irradiation, ultrasonic vibration, and light irradiation + ultrasonic vibration;

[0036] Fig.12 The test results of photocatalytic degradation of Rhodamine B in Example 2 and Comparative Example 1 of the present invention are shown in FIG.

[0037] Fig.13It is the first-order kinetic fitting diagram of the photocatalytic degradation of Rhodamine B in Example 2 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0039] Example 1

[0040] Preparation of Cu 2+ Doped PbBiO2Br catalyst:

[0041] S1: Use an electronic analytical balance to accurately weigh 1.4552 g of bismuth nitrate pentahydrate and dissolve it in 10 mL of 6 mol / L nitric acid solution. Then add 0.20 g of polyvinyl pyrrolidone and 50 mL of deionized water and stir for 30 minutes.

[0042] S2: Weigh 0.9936 g of lead nitrate and 0.3087 g of sodium bromide, add to the above mixed solution and continue magnetic stirring for 30 minutes.

[0043] S3: During the stirring process, add 0.025 mL of 0.6 mol / L copper nitrate solution, mix well, slowly add 25 mol / L sodium hydroxide solution, adjust the pH of the mixture to 11, and continue stirring for 20 minutes.

[0044] S4: The obtained suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to a total volume of 80 mL, and the suspension was hydrothermally reacted at 160°C for 12 hours. After the reaction was completed, it was cooled to room temperature, the supernatant was poured out, and the precipitate was centrifuged and washed three times with a mixed solution of ultrapure water and alcohol. Finally, the precipitate was placed in an oven and dried at 60°C for 12 hours.

[0045] S5: The precipitate was then calcined in a muffle furnace at 400°C for 2 hours to obtain Cu 2+ Doped PbBiO2Br catalyst, in which Cu 2+ The molar ratio to PbBiO2Br is 0.5%.

[0046] Example 2

[0047] Preparation of Cu 2+ Doped PbBiO2Br catalyst:

[0048] S1: Use an electronic analytical balance to accurately weigh 1.4552 g of bismuth nitrate pentahydrate and dissolve it in 10 mL of 6 mol / L nitric acid solution. Then add 0.20 g of polyvinyl pyrrolidone and 50 mL of deionized water and stir for 30 minutes.

[0049] S2: Weigh 0.9936 g of lead nitrate and 0.3087 g of sodium bromide, add to the above mixed solution and continue magnetic stirring for 30 minutes.

[0050] S3: During the stirring process, add 0.050 mL of 0.6 mol / L copper nitrate solution. After mixing evenly, slowly add 25 mol / L sodium hydroxide solution dropwise to adjust the pH of the mixture to 11 and continue stirring for 20 minutes.

[0051] S4: The obtained suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to a total volume of 80 mL, and the suspension was hydrothermally reacted at 160°C for 12 hours. After the reaction was completed, it was cooled to room temperature, the supernatant was poured out, and the precipitate was centrifuged and washed three times with a mixed solution of ultrapure water and alcohol. Finally, the precipitate was placed in an oven and dried at 60°C for 12 hours.

[0052] S5: The precipitate was then calcined in a muffle furnace at 400°C for 2 hours to obtain Cu 2+ Doped PbBiO2Br catalyst, in which Cu 2+ The molar ratio to PbBiO2Br is 1%.

[0053] Example 3

[0054] Preparation of Cu 2+ Doped PbBiO2Br catalyst:

[0055] S1: Use an electronic analytical balance to accurately weigh 1.4552 g of bismuth nitrate pentahydrate and dissolve it in 10 mL of 6 mol / L nitric acid solution. Then add 0.20 g of polyvinyl pyrrolidone and 50 mL of deionized water and stir for 30 minutes.

[0056] S2: Weigh 0.9936 g of lead nitrate and 0.3087 g of sodium bromide, add to the above mixed solution and continue magnetic stirring for 30 minutes.

[0057] S3: During the stirring process, add 0.075 mL of 0.6 mol / L copper nitrate solution. After mixing evenly, slowly add 25 mol / L sodium hydroxide solution dropwise to adjust the pH of the mixture to 11 and continue stirring for 20 minutes.

[0058] S4: The obtained suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to a total volume of 80 mL, and the suspension was hydrothermally reacted at 160°C for 12 hours. After the reaction was completed, the suspension was cooled to room temperature, the supernatant was discarded, and the precipitate was centrifuged and washed three times with a mixed solution of ultrapure water and alcohol. Finally, the precipitate was placed in an oven and dried at 60°C for 12 hours.

[0059] S5: The precipitate was then calcined in a muffle furnace at 400°C for 2 hours to obtain Cu 2+ Doped PbBiO2Br catalyst, in which Cu 2+ The molar ratio to PbBiO2Br is 1.5%.

[0060] Example 4

[0061] Preparation of Cu 2+ Doped PbBiO2Br catalyst:

[0062] S1: Use an electronic analytical balance to accurately weigh 1.4552 g of bismuth nitrate pentahydrate and dissolve it in 10 mL of 6 mol / L nitric acid solution. Then add 0.20 g of polyvinyl pyrrolidone and 50 mL of deionized water and stir for 30 minutes.

[0063] S2: Weigh 0.9936 g of lead nitrate and 0.3087 g of sodium bromide, add to the above mixed solution and continue magnetic stirring for 30 minutes.

[0064] S3: During the stirring process, add 0.100 mL of 0.6 mol / L copper nitrate solution, mix well, slowly add 25 mol / L sodium hydroxide solution, adjust the pH of the mixture to 11, and continue stirring for 20 minutes. The resulting suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to a total volume of 80 mL of the suspension, and hydrothermally reacted at 160 ° C for 12 hours. After the reaction is completed, cool to room temperature, pour off the supernatant, and centrifuge and wash the precipitate 3 times with a mixed solution of ultrapure water and alcohol. Finally, the precipitate was placed in an oven and dried at 60 ° C for 12 hours.

[0065] S4: The precipitate was then calcined in a muffle furnace at 400°C for 2 hours to obtain Cu 2+ Doped PbBiO2Br catalyst, in which Cu 2+ The molar ratio to PbBiO2Br is 2%.

[0066] Comparative Example 1

[0067] Use an electronic analytical balance to accurately weigh 1.4552 g of bismuth nitrate pentahydrate, dissolve it in 10 mL of 6 mol / L nitric acid solution, then add 0.2 g of polyvinyl pyrrolidone and 50 mL of deionized water, and stir for 30 minutes. Then weigh 0.9936 g of lead nitrate and 0.3087 g of sodium bromide, add the above mixed solution and continue magnetic stirring for 30 minutes. Slowly add 25 mol / L sodium hydroxide solution, adjust the pH of the mixed solution to 11, and continue stirring for 20 minutes. The resulting suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to a total volume of 80 mL, and hydrothermally reacted at 160 ° C for 12 hours. After the reaction was completed, it was cooled to room temperature, the supernatant was poured off, and the precipitate was centrifuged and washed 3 times with a mixed solution of ultrapure water and alcohol. Finally, the precipitate was placed in an oven and dried at 60 °C for 12 h, and then calcined in a muffle furnace at 400 °C for 2 h to obtain the target product PbBiO2Br.

[0068] Performance testing and results:

[0069] X-ray diffraction (XRD) analysis was performed using a D8 Advance (BRUKER AXS GMBH, Germany) X-ray diffractometer with Cu Kα radiation (40 kV / 40 mA).

[0070] Raman spectroscopy was performed on a Renishaw RM1000 spectrometer with an argon ion laser (514.5 nm) as the excitation source.

[0071] UV-visible diffuse reflectance spectroscopy (DRS) was performed on a UV-visible spectrophotometer (Agilent Cary5000) with BaSO4 as the reference sample.

[0072] X-ray photoelectron spectroscopy (XPS) analysis was performed using a Thermo Scientific ESCALAB 250Xi microprobe instrument with Al-Kα radiation as the light source.

[0073] Scanning electron microscopy (SEM) analysis used a field emission scanning electron microscope (Hitachi S-4800) with the accelerating voltage set to 5 kV.

[0074] Transmission electron microscopy (TEM) analysis was performed using a JEM-2010F transmission electron microscope with an accelerating voltage of 200 kV.

[0075] The catalysts obtained in Example 2 and Comparative Example 1 were subjected to XRD, XPS, Raman, and DRS tests. The results are as follows: Figure 1-3 as well as Figure 5 shown.

[0076] The catalysts obtained in Example 3 and Comparative Example 1 were tested by SEM and TEM. Figure 4 shown.

[0077] Figure 1 The XRD spectra of Example 2 and Comparative Example 1 are shown. It can be observed that Cu 2+ After doping, the diffraction peak of PbBiO2Br shifts to a higher diffraction angle, indicating that the lattice of the material shrinks. Considering that the atomic radius of Cu is smaller than that of Pb and Bi, this result proves that Cu is doped into the PbBiO2Br lattice. Figure 2 The Raman spectra of Example 2 and Comparative Example 1 show that the Raman signal of PbBiO2Br is weakened by Cu doping, which can be attributed to the influence of Cu doping. XPS characterization ( Figure 3 ) confirmed that the Cu 2+ existence. Figure 4 SEM of Example 3 ( Figure 4 d) and TEM ( Figure 4 SEM of comparative example 1 ( Figure 4 Part a) and TEM ( Figure 4 The images in the bc part further show that Cu 2+ The doping of has little effect on the morphology of PbBiO2Br, but its lattice order is reduced. Figure 5 The DRS spectra of Example 2 and Comparative Example 1 are shown. Cu 2+ The doping of PbBiO2Br enhances the absorption of PbBiO2Br in the visible light region, and the band gap decreases from 2.52 eV to 2.48 eV.

[0078] Photocatalytic nitrogen fixation experiment

[0079] 1) Weigh 0.1 g of each catalyst prepared in Examples 1-4 and Comparative Example 1, pour them into 150 mL beakers, and then add 95 mL of ultrapure water and 5 mL of anhydrous methanol as sacrificial agents (5% by volume, i.e., 5 vol%).

[0080] 2) Seal the mouth of the beaker with plastic wrap, seal and stir for 1 hour to ensure adsorption-desorption equilibrium, take sample No. 0 (take 5.0 mL from a 10 mL centrifuge tube), then remove the plastic wrap, place the beaker on a magnetic stirrer, and react under irradiation of a 350 W xenon lamp (Perfect, PLS-SXE300), take a sample every 1 hour, and take 5 samples in sequence. The entire experiment takes 5 hours.

[0081] 3) Centrifuge to separate the catalyst, take the supernatant, add 20 µL of national standard masking agent potassium sodium tartrate with a pipette, react for 10 minutes, and then add 30 µL of Nessler's reagent;

[0082] 4) After standing for 12 min, use a UV-visible spectrophotometer to measure the absorbance of samples 0 to 5 in sequence and record the absorbance value at 420 nm. Finally, use NH4 + The standard curve determines the ammonia content, and the result is as follows Figure 6 As shown (the blank sample is the sample without adding catalyst, and the rest of the steps are the same as other groups).

[0083] like Figure 6 As shown, it can be observed that Comparative Example 1 has a certain photocatalytic nitrogen fixation performance, and the ammonia generation rate is 81.5 μmol L -1 g -1 h -1 Compared with Comparative Example 1, Examples 1-4 doped with Cu 2+ The photocatalytic nitrogen fixation performance of the ion post-catalyst was significantly improved. The photocatalytic nitrogen fixation performance of Example 2 was the most outstanding, with an ammonia generation rate of 293 μmol L -1 g -1 h -1 , which is 3.6 times that of comparative example 1.

[0084] Photocatalytic nitrogen fixation cycle test implementation:

[0085] After the photocatalytic nitrogen fixation experiment of Example 2, the sample was centrifuged, washed three times with deionized water and anhydrous ethanol, and then heated at 60 o C oven, and then use the recovered catalyst to continue the second cycle experiment. This was repeated five times, and the results were as follows: Figure 7 shown.

[0086] like Figure 7 As shown, after five cycles of use, the catalytic activity of Example 2 remains unchanged, proving that the material has high stability.

[0087] Ultrasonic vibration catalytic nitrogen fixation experiment:

[0088] The ultrasonic vibration nitrogen fixation experiment was carried out on Example 2 and Comparative Example 1. The difference from the photocatalytic nitrogen fixation experiment was that the reaction condition of "reacting under irradiation of a 350 W xenon lamp" was changed to "placing the beaker containing the reaction solution in an ultrasonic cleaning machine (JP-020S, 120 W / 40 Hz) for vibration catalytic reaction". The experimental results are shown in Figure 2. Figure 8-9 shown.

[0089] Light-ultrasound vibration synergistic catalytic nitrogen fixation experiment:

[0090] The light-ultrasonic vibration nitrogen fixation experiment was carried out on Example 2 and Comparative Example 1. The difference from the photocatalytic nitrogen fixation experiment is that the reaction condition of "reacting under irradiation of a 350 W xenon lamp" was changed to "placing the beaker containing the reaction solution under irradiation of a 120 W ultrasonic cleaning machine and a 350 W xenon lamp at the same time to carry out a light-vibration synergistic catalytic nitrogen fixation reaction". The experimental results are shown in FIG. Figure 8-9 shown.

[0091] like Figure 8-9 As shown in the figure, compared with Comparative Example 1, Example 2 showed better photo-vibration catalytic performance under the conditions of light irradiation and ultrasonic vibration, and the nitrogen fixation rate reached 389 μmol L -1 g -1 h -1 , which are 1.3 and 3.0 times that of photocatalysis and vibration catalysis, respectively. It is worth noting that comparative example 1 also reflects the synergistic catalytic effect of light-vibration catalysis. However, its synergistic catalytic nitrogen fixation rate is only 96.1µmol L -1 g -1 h -1 , while the synergistic nitrogen fixation rate of Example 2 is 4.0 times that of Example 2.

[0092] AC impedance test:

[0093] Electrochemical impedance spectroscopy (EIS) analysis and transient current response were performed on a CHI 660E electrochemical workstation. A standard three-electrode cell configuration was used, in which the catalyst was used as the working electrode, Ag / AgCl (saturated KCl solution) was used as the reference electrode, and a platinum electrode was used as the counter electrode. The electrolyte used was a 0.5 mol / L Na2SO4 aqueous solution. The working electrode was prepared as follows: a small amount of catalyst was weighed, and an appropriate amount of naphthol and ethanol were added and mixed and ground, and then coated on ITO glass and dried. The coating area was 1.0×1.0 cm. The test results are shown in the figure. Fig.10 shown.

[0094] like Fig.10 As shown, compared with Comparative Example 1, Example 2 has a smaller interface resistance and a faster electron migration rate, which enables more electrons and holes to participate in the photocatalytic reaction. Fig.11 The transient current response of Example 2 under light, ultrasound, and light + ultrasonic vibration is demonstrated. It can be observed that the current intensity is greater under the combined action of light and vibration, confirming that the catalyst prepared in Example 2 has the synergistic effect of light and vibration.

[0095] Photocatalytic degradation of Rhodamine B (RhB) experiment:

[0096] 1) Prepare a 10 mg / L Rhodamine B (RhB) solution.

[0097] 2) Weigh 0.10 g of each catalyst prepared in Example 2 and Comparative Example 1, add 100 mL of the target degradation solution prepared in step (1) respectively, and stir magnetically for 60 minutes. After the sample materials are evenly dispersed, place the beaker under a 350 W xenon lamp to carry out a photocatalytic degradation experiment of RhB.

[0098] 3) The total duration of the photocatalytic degradation activity test was 1.5 hours. 3 mL of the reaction solution was drawn every 15 minutes. After centrifugation, the absorbance at 554 nm was measured using a UV-visible spectrophotometer. The test results are as follows: Figure 12-13 As shown (the blank sample is the sample without adding catalyst, and the rest of the steps are the same as the experimental group).

[0099] like Figure 12-13 As shown, compared with Comparative Example 1, the Cu 2+ The doped PbBiO2Br catalyst also has good performance in photocatalytic degradation of pollutants. 2+ Doped PbBiO2Br catalyst has great application potential in the fields of nitrogen fixation and RhB dye degradation.

[0100] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A Cu 2+ Doped PbBiO2Br catalyst, characterized in that In the chemical composition, Cu 2+ The molar ratio to PbBiO2Br is x%, where 0.5≤x≤2.

2. A Cu according to claim 1 2+ Doped PbBiO2Br catalyst, characterized in that Cu 2+ The molar ratio to PbBiO2Br is 1%.

3. A Cu according to claim 2 2+ Doped PbBiO2Br catalyst, characterized in that The energy band gap of the catalyst is 2.48 eV.

4. A Cu 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: The steps include: S1: dissolving bismuth nitrate in a first solvent, and then mixing the mixture with polyvinyl pyrrolidone and water; S2: uniformly mixing the mixed solution obtained in step S1 with lead nitrate and sodium bromide; S3: uniformly mixing the mixed solution obtained in step S2 and copper nitrate, adding a pH adjuster, adjusting the pH of the mixed solution to 11, and uniformly mixing; S4: subjecting the mixed solution obtained in step S3 to a hydrothermal reaction at 170-180° C. for 10-14 h, cooling, performing solid-liquid separation on the obtained reaction solution, washing the solid, and drying; S5: calcining the solid obtained in step S4 at a high temperature to obtain the Cu as described in any one of claims 1 to 3 2+ Doped PbBiO2Br catalyst.

5. A Cu according to claim 4 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: In the step S1, the first solvent is nitric acid; the concentration of the nitric acid is 6 mol / L.

6. A Cu according to claim 5 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: The molar ratio of the bismuth nitrate to the nitric acid is 1:1.5-2.

5.

7. A Cu according to claim 4 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: The molar ratio of the bismuth nitrate, the lead nitrate and the sodium bromide is 1:1:1; the molar ratio of the added mass of the polyvinyl pyrrolidone to the bismuth nitrate is 1.5-2.5 g:0.03 mol.

8. A Cu according to claim 4 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: In step S4, the volume ratio of the mole of bismuth nitrate to the solution in the hydrothermal reaction is 2.9-3.1 mmol:80 mL.

9. A Cu according to claim 4 2+ The preparation method of the doped PbBiO2Br catalyst is characterized in that: In the step S5, the high temperature calcination temperature is 350-450° C. and the calcination time is 1.5-2.5 hours.

10. A kind of Cu 2+ The application of doped PbBiO2Br catalyst is characterized in that: Cu as described in any one of claims 5-9 2+ The doped PbBiO2Br catalyst is used for photocatalytic and / or ultrasonic catalytic nitrogen fixation and photocatalytic degradation of RhB.